On Social Trust, Financing Environment and Enterprises’ Short-Term Funds used for Long-Term Investment (SFLI) Decision - Zhulin Wang (Forest Chemicals Review)
In this paper, China’s listed a-share enterprises from 2007 to 2019 are taken as the research sample. Based on the perspective of financing constraints and debt financing cost, this study empirically analyzes the impact of social trust on SFLI (hereinafter SFLI). The results show that social trust can reduce the occurrence of SFLI, mainly by lessening financing constraints and reducing debt financing costs. Meanwhile, the relationship among managerial competence, industrial policy and social trust is substitution, which can control the degree of SFLI to a certain extent by mutual choice. This paper enriches the research in the field of social trust and the influencing factors of short-term fund for long-term investment, and has a certain reference significance for managers to arrange the investment and financing period reasonably.